A three-dimensional hydrodynamic model with generic vertical coordinate - Martins, Flávio Augusto Bastos da Cruz (2009)
A three-dimensional primitive equation model and its application to a tidal estuary is described. The model solves the primitive equations for incompressible fluids with Boussinesq and hydrostatic approximations. The discretization is based on the finite volume method and allows a general vertical coordinate. The computational code is implemented in such a way that different vertical coordinates can be used in different parts of the domain. The model was designed to be able to simulate the flow both in the open ocean and in coastal and estuarine zones and can be coupled in a simple way to ecological models. The model was implemented successfully in several estuarine and coastal areas. Results are show for the Sado estuary in Portugal to illustrate model accuracy and potential. Quantitative validation is based on field data (water levels and velocities) while qualitative verification is based on the analysis of secondary flows.